Tracking direct and indirect impact on technology and policy of transformative research via ego citation network - Li Xian; Hu Xiaojun (Journal of Data and Information Science, 2024)
The disseminating of academic knowledge to nonacademic audiences partly relies on the transition of subsequent citing papers. This study aims to investigate direct and indirect impact on technology and policy originating from transformative research based on ego citation network.